Analisis Faktor Eksistensi Tren Thrifting Sebagai Gaya Konsumsi Fashion Dikalangan Generasi Millenial - syakir, alfin (Universitas Negeri Surabaya, 2024)
The phenomenon of thrifting has become a new fashion culture among millennials, especially during the COVID-19 pandemic, as it is considered a cost-saving lifestyle. Thrifting involves buying secondhand items, particularly imported ones, which has led to a decrease in interest in local products. The government has even issued a ban on thrifting due to health concerns. This research aims to analyze the factors that have led to the emergence of this trend and to understand its impact on the younger generation. The research method used is descriptive research with a literature approach, which involves collecting data through literature studies such as articles, journals, and books. The results of the study show that the sale of secondhand clothing has created a new fashion culture that has value for millennials who have a contemporary lifestyle. The factors that have contributed to the trend of thrifting include the COVID-19 pandemic, the price factor, and the social effect of influencers. The study concludes that thrifting has become a popular trend among millennials, and it is essential to understand its impact on society.